Pelatihan Keterampilan Komunikasi dalam Akomodasi Pondok Wisata pada Warga Desa Wisata Besani - Yulius, Kevin Gustian; Wowor, Wulanmeiaya; Sianipar, Rosianna; Nathalia, Theodosia C.; Parera, Sisilia Chelsye (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
Communication Skills Training in Homestay Business for Residents of Desa Wisata Besani Tourism has become a crucial sector in the local economic development and cultural preservation in Indonesia. This article discusses a training activity on communication skills within the context of homestay accommodation for the residents of Besani Tourism Village in Batang Regency, Central Java. The training, successfully conducted in November 2023, involved 28 participants from various segments of society, including homestay operators and members of the Tourism Awareness Group (Pokdarwis). Through lectures and simulations, the pretest and post-test results showed a significant improvement from 18-36% to 89-100% in the understanding of communication skills. The outcomes of this training are expected to assist Besani Tourism Village in developing sustainable homestay businesses by engaging in collaborations with various stakeholders, enhancing management skills, digital marketing, and environmental conservation. This article provides new insights into the importance of communication skills training in the context of homestay accommodation within rural communities and offers recommendations for tourism village officials and residents of Besani Tourism Village to continue their efforts in local tourism development with enthusiasm for collaboration and active participation.